2018
DOI: 10.2337/dc18-0243
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Contrasts Between Youth and Adults With Impaired Glucose Tolerance or Recently Diagnosed Type 2 Diabetes: II. Observations Using the Oral Glucose Tolerance Test

Abstract: The balance between insulin sensitivity and β-cell responses differs between youth and adults with IGT or recently diagnosed type 2 diabetes. Despite similar postload glucose levels, youth demonstrate greater C-peptide and insulin responses that exceed what is needed to compensate for their lower insulin sensitivity. Longitudinal studies are required to determine whether this feature contributes to a more rapid decline in β-cell function in youth with dysglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…By the end of the study, girls had restored insulin sensitivity and normalised insulin secretion, whereas boys had persistently increased insulin resistance and exhibited a decline in beta cell reserve and increased fasting glucose levels [67]. Loss of glucose-stimulated insulin secretion was also observed in the youth type 2 diabetes cohort in the National Institute of Health (NIH) Restoring Insulin Secretion (RISE) study (no sex differences have been reported to date in the 91 participants) [68]. Thus, obesity, insulin resistance and insulin hypersecretion [61] are likely to be key mediators of type 2 diabetes in youth.…”
Section: Mechanism Of Type 2 Diabetes Onset In Youthmentioning
confidence: 90%
“…By the end of the study, girls had restored insulin sensitivity and normalised insulin secretion, whereas boys had persistently increased insulin resistance and exhibited a decline in beta cell reserve and increased fasting glucose levels [67]. Loss of glucose-stimulated insulin secretion was also observed in the youth type 2 diabetes cohort in the National Institute of Health (NIH) Restoring Insulin Secretion (RISE) study (no sex differences have been reported to date in the 91 participants) [68]. Thus, obesity, insulin resistance and insulin hypersecretion [61] are likely to be key mediators of type 2 diabetes in youth.…”
Section: Mechanism Of Type 2 Diabetes Onset In Youthmentioning
confidence: 90%
“…The Restoring Insulin Secretion (RISE) Study has, for the first time, directly compared insulin sensitivity, beta cell function and treatment response in adults and youths with IGT or recently diagnosed type 2 diabetes [98][99][100]. At baseline, youths were more insulin resistant and had greater insulin responses for any degree of insulin sensitivity despite similar levels of obesity and dysglycaemia as compared with adults [98,99]. Further, in youths with IGT and type 2 diabetes, beta cell function progressively deteriorated while on metformin alone or insulin glargine followed by metformin [100]; this deterioration was not observed in adults.…”
Section: Youths Vs Adults: New Insights Into the Pathophysiology Of Dmentioning
confidence: 99%
“…At the same time, the unabated increase in childhood obesity is also tightly linked to the emergence of T2D as a new type of pediatric diabetes [92]. Early results from the RISE study show the clinical course is markedly different in adolescents compared to adults suggesting the need for further research to better prevent and manage this unique and increasingly important population [93][94][95][96].…”
Section: Areas For Future Researchmentioning
confidence: 99%